GENERATION MEAN ANALYSIS USING GENERATION VARIANCE IN DURUM WHEAT TRAITS (Triticum durum L.) - Askander, H. S. Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The present investigation was conducted to estimate the gene action effects in some traits of durum wheat by using crosses two generation of wheat (Albit-9 X omgenil-3) through generation mean analysis during growing season 2016-2017, at Field Crops Department, Collage of Agricultural Engineering Sciences, University of Duhok. The analysis of variance showed significant differences between generations mean for studied traits except spike length which did not significant. The mean value of F1 generation was higher than the respect parents (P1 and P2) F2, Bc1 and Bc2 for most of studied traits in wheat crosses. The results of gene effect shown that the dominance gene effects were significant and positive with all studied traits, whereas additive gene effect did not significant for all traits except plant height and number of grain per spike, also The results exhibited that the dominance and additive X additive variance was positive for all traits this mean complementary gene effect controlling these traits, regarding of broad and narrow sense heritability. The results indicate that broad sense value was more than the narrow sense heritability. Heterosis in F1 cross over mid parents was recorded a positive value (9.672, 8.112) for plant height and grain yield per plant, while inbreeding depression was measured as reduction in performance of F2 generation a positive results were obtained for all traits.